Dynamic robust path-following control of UVMS subject to manipulator disturbance - Jiao, Huifeng; Wang, Guanhua; Wang, Yintao; Mao, Zhaoyong (Journal of physics. Conference series, 2024)
This study addresses path-following control issue of underwater vehicle-manipulator systems (UVMS) in the presence of manipulator disturbances. It considers disturbance forces arising from manipulator position changes, including restorative forces and coupling forces, to achieve precise UVMS path-following control. By analysing the variations in the center of mass and buoyant center of manipulator links during motion, the corresponding restorative torque is deduced, and disturbance forces are calculated. Additionally, joint coupling forces generated during manipulator startup, braking, and rotation are taken into account. These aspects collectively yield the expression for disturbance forces. Subsequently, adaptive sliding mode control are employed to achieve accurate control of the UVMS system. This study effectively addresses the issue of UVMS body control under manipulator disturbances. By analysing the motion of manipulator links, the disturbance forces exerted by the manipulator on the UVMS are identified, offering insights for similar control challenges arising from manipulator disturbances. Simulation results are conducted to show the effectiveness of the proposed control method.